The State, the performing arts and the taxpayer : applied econometric essays on the German cultural sector - Martins, António Pedro Crespo (Trinity College (Dublin, Ireland). Department of Economics, 2008)
This research work investigates the relation between the State, the performing arts organisations and the taxpayer. The overall area of interest is taxation and public policy, in the form of public support for the arts. The empirical research is applied to Germany, using German datasets. Chapter 1 describes cultural policy and the performing arts sector in Germany. This sets the framework for the empirical studies. Chapter 2 studies the cost factors of German performing arts, by focusing on public theatres and orchestras. The main goal is to understand the cost structure of arts organisations, and about ways in which the performing arts firms may be able to rearrange their resources to lower their costs and improve their profitability. Differences in the availability of data require different empirical models to be considered for public theatres and for Orchestras. The models were estimated using OLS.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin